Genome-wide analysis of copy-number variation in humans with cleft lip and/or cleft palate identifies COBLL1, RIC1, and ARHGEF38 as clefting genes - Lansdon, Lisa A.; Dickinson, Amanda; Arlis, Sydney; Liu, Huan; Hlas, Arman; Hahn, Alyssa; Bonde, Greg; Long, Abby; Standley, Jennifer; Tyryshkina, Anastasia; Wehby, George; Lee, Nanette R.; et al. (American journal of human genetics, 2023)
Cleft lip with or without cleft palate (CL/P) is a common birth defect with a complex, heterogeneous etiology. It is well established that common and rare sequence variants contribute to the formation of CL/P, but the contribution of copy-number variants (CNVs) to cleft formation remains relatively understudied. To fill this knowledge gap, we conducted a large-scale comparative analysis of genome-wide CNV profiles of 869 individuals from the Philippines and 233 individuals of European ancestry with CL/P with three primary goals: first, to evaluate whether differences in CNV number, amount of genomic content, or amount of coding genomic content existed within clefting subtypes; second, to assess whether CNVs in our cohort overlapped with known Mendelian clefting loci; and third, to identify unestablished Mendelian clefting genes. Significant differences in CNVs across cleft types or in individuals with non-syndromic versus syndromic clefts were not observed; however, several CNVs in our cohort overlapped with known syndromic and non-syndromic Mendelian clefting loci. Moreover, employing a filtering strategy relying on population genetics data that rare variants are on the whole more deleterious than common variants, we identify several CNV-associated gene losses likely driving non-syndromic clefting phenotypes. By prioritizing genes deleted at a rare frequency across multiple individuals with clefts yet enriched in our cohort of individuals with clefts compared to control subjects, we identify COBLL1, RIC1, and ARHGEF38 as clefting genes. CRISPR-Cas9 mutagenesis of these genes in Xenopus laevis and Danio rerio yielded craniofacial dysmorphologies, including clefts analogous to those seen in human clefting disorders. The contribution of copy-number variants to cleft lip with or without cleft palate (CL/P) has been relatively understudied. Using a strategy to identify likely higher effect size microdeletions, we identify COBLL1, RIC1, and ARHGEF38 as genes associated with CL/P that play important roles in vertebrate craniofacial development.